Ribosomal DNA heterochromatin in plants - Neves, N. (2005)
The aim of this review is to integrate earlier results and recent findings to present the current state-of-the art vision concerning the dynamic behavior of the ribosomal DNA (rDNA) fraction in plants. The global organization and behavioral features of rDNA make it a most useful system to analyse the relationship between chromatin topology and gene expression patterns. Correlations between several heterochromatin fractions and rDNA arrays demonstrate the heterochromatic nature of the rDNA and reveal the importance of the genomic environment and of developmental controls in modulating its dynamics